Paciente masculino de 67 años de edad con cirrosis hepática y diabetes mellitus tipo 2. - Chinga Ramos, Jheslyn Estrella (2020)
It is defined as type 2 diabetes mellitus to a chronic disease, caused by multiple aetiologies characterized by hyperglycemia disturbances in the metabolism of carbohydrates, fats and proteins with effects on the secretion and action of insulin. On the other hand, liver cirrhosis is a progressive and irreversible chronic disease characterized by the numbering of nodules surrounded by an area of fibrosis that alter intrahepatic circulation. The general objective was to improve the quality of life of the overweight patient, liver cirrhosis and type 2 diabetes mellitus through nutritional intervention by applying therapeutic dietary techniques. The patient's clinical history, food anamnesis, clinical examination and biochemical examinations were taken into account in the development of the clinical case. The present case study is of a 67-year-old overweight patient, hepatic cirrhosis and type 2 diabetes mellitus. The comprehensive nutritional diagnosis of the overweight older adult male patient, increased vascular risk with food sufficiency and macro and micronutrient energy was developed. Odin: type 2 diabetes mellitus and anemia. Evidenced by a BMI of 29.29 kg/m2, 133 cm abdominal circumference and food frequency which demonstrates excessive consumption of simple carbohydrates and does not consume all the nutrients to be ingested through food. A personalized dietary plan was made of a diet of 1515 calories daily hypocarbonate hypocaloric high in hyper ferric fiber fractionated in 6 main 3 takes and 3 snacks had good results as it improved the nutritional status and lifestyle of the patient.